Income Generation for Vulnerable Group Development (IGVGD): December 1991 - BRAC (© BRAC, 2016)
List of Abbreviations/Administrative Structure; lntroduction; Background; Objectives or the Programme; The Programme Model; Credit; Programme Management; Monitoring; Conclusion; Appendix;